Impact of Goal-Directed Therapy on Delayed Ischemia After Aneurysmal Subarachnoid Hemorrhage: Randomized Controlled Trial. Issue 8 (August 2020) - Anetsberger, Aida; Gempt, Jens; Blobner, Manfred; Ringel, Florian; Bogdanski, Ralf; Heim, Markus; Schneider, Gerhard; Meyer, Bernhard; Schmid, Sebastian; Ryang, Yu-Mi; Wostrack, Maria; Schneider, Jürgen; et al.
Abstract : Background and Purpose: Delayed cerebral ischemia (DCI) is the most important cause for a poor clinical outcome after a subarachnoid hemorrhage. The aim of this study was to assess whether goal-directed hemodynamic therapy (GDHT), as compared to standard clinical care, reduces the rate of DCI after subarachnoid hemorrhage. Methods: We conducted a prospective randomized controlled trial. Patients >18 years of age with an aneurysmal subarachnoid hemorrhage were enrolled and randomly assigned to standard therapy or GDHT. Advanced hemodynamic monitoring and predefined GDHT algorithms were applied in the GDHT group. The primary end point was the occurrence of DCI. Functional outcome was assessed using the Glasgow Outcome Scale (GOS) 3 months after discharge. Results: In total, 108 patients were randomized to the control (n=54) or GDHT group (n=54). The primary outcome (DCI) occurred in 13% of the GDHT group and in 32% of the control group patients (odds ratio, 0.324 [95% CI, 0.11–0.86]; P =0.021). Even after adjustment for confounding parameters, GDHT was found to be superior to standard therapy (hazard ratio, 2.84 [95% CI, 1.18–6.86]; P =0.02). The GOS was assessed 3 months after discharge in 107 patients; it showed more patients with a low disability (GOS 5, minor or no deficits) than patients with higher deficits (GOS 1–4) in the GDHT group compared with the control group (GOS 5, 66% versus 44%; GOS 1–4, 34% versus 56%; P =0.025). There was no significant difference in mortality between the groups. Conclusions: GDHT reduced the rate of DCI after subarachnoid hemorrhage with a better functional outcome (GOS=5) 3 months after discharge. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01832389. Abstract : Supplemental Digital Content is available in the text.